Law Enforcement to Transcendental Based of Paramedic Doctoroid Practices in Health Service - Siti Soekiswati; Absori Absori (Journal of Transcendental Law, 2019)
Purpose of the study: This article aims to discuss the paramedic doctoroid practices in primary health care in Community Health Center conducted by paramedic doctors.Methodology: This research is socio-legal research; research on law application, viewing law acting as law in action, which involves the interrelation between law and social institutions.Main Findings: Delegation of duty policies under the roof of paramedic doctoroid practices in health services in Community Health Center. This research is a socio-legal aimed at uncovering the phenomenon of paramedic doctoroid practices.Applications of the study: The current study provides criticism for the government in creating inconsistent policies, poor supervision, and law enforcement behind doctoroid practice persistence.Novelty/Originality of the study: the concept of law enforcement is based on the philosophy of the first principle of Pancasila as the Indonesian ideology, transcendental-based law enforcement.